Decomposição de suplemento mineral por piroidrólise para a determinação de halogênios - Taflick, Ticiane (2006)
In this work it is proposed a method for fluorine (F), bromine (Br) and iodine (I) determination in mineral-feedingstuff after sample decomposition by pyrohydrolysis. Fluoride is determined potentiometrically by means of ion selective electrode (ISE) while Br and I are determined by inductively coupled plasma mass spectrometry (ICP-MS). The sample decomposition is based on heating the sample at ca. of 1100 0C in presence of water vapor and vanadium pentoxide (V2O5) used as accelerator of the pyrohydrolysis reaction. During the heating step the analytes are vaporized and released from the sample and react with water vapor producing HF, HBr and HI. While HF vapor is simply condensed, HBr and HI need to be condensed and then trapped in a basic solution. Parameters like amount of sample + accelerator, gas flow rate (air), decomposition time, kind and concentration of trapping solution (for Br and I) were investigated for sample decomposition by pyrohydrolysis. It was observed that best results are obtained when the amount of sample + accelerator is 1 + 5, the sample decomposition is carried out during 10 min (producing approximately 10 mL of condensed solution) and the gas flow rate is 200 mL min-1. Tetramethylammonium hydroxide (TMAH), ammonium hydroxide (NH4OH) and a mixture of sodium carbonate/sodium bicarbonate (Na2CO3/NaHCO3) were tested as trapping solution for Br and I. Best analyte recoveries were obtained by using a 50 mmol L-1 sodium carbonate/sodium bicarbonate solution. Therefore, the aforementioned conditions were established in the proposed method. The limits of detection (LD) of F, Br and I were 12.0 μg g-1, 0.28 μg g-1 and 0.68 μg g-1, respectively, while the relative standard deviation (RSD) was typically lower than 14%. The method was validated by analyte recovery tests, whose recoveries ranged from 88% to 109%. The method was applied for the determination of F, Br and I in several samples whose concentrations were in the range of 600 to 1800 μg g-1, 26 to 30 μg g-1 and 10 to 58 μg g-1 for F, Br and I, respectively